Censorship detected in SY (Syria) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Syria. Data sourced from CensoredPlanet.
Censorship Incident ID: SY-2026-0002. Severity: critical. Confidence: 65%